PERAN GURU PAI DALAM IMPLEMENTASI GERAKAN LITERASI SEKOLAH DI SMPN 5 TELUK KUANTAN - Meta Huljannah (Universitas Islam Kuantan Singingi, 2020)
This research is motivated by the implementation of Gerakan Literasi Sekolah (GLS) as a derivative of the Gerakan Literasi Nasional (GLN) in March 2016 based on Minister of Education and Culture Regulation No. 23 of 2015 concerning the Growth of Human Rights by intensifying the National Literacy Movement. At SMP Negeri 5 Teluk Kuantan, GLS has been implemented as an integral part of the Kurikulum 2013 where there is the role of subject teachers, especially Islamic Education (PAI) subjects who teach in class VIII. But it cannot be known with certainty whether the PAI subject teacher has optimized its role in the implementation of GLS in grade VIII students at SMP Negeri 5 Teluk Kuantan. This study aims to determine the optimal role of Islamic Education teachers in implementing Gerakan Literasi Sekolah (GLS) in grade VIII students at SMP Negeri 5 Teluk Kuantan. This research is a qualitative descriptive with the subject of the study being the subject of Islamic Education (PAI) subjects. Data collection techniques used were observation, interviews and documentation. The results showed that the role of Islamic Education teachers in the implementation of Gerakan Literasi Sekolah (GLS) of Grade VIII students in SMP Negeri 5 Teluk Kuantan was not optimal despite efforts to implement this movement in their subjects.